2022
DOI: 10.3389/fphys.2022.963762
|View full text |Cite
|
Sign up to set email alerts
|

Caloric restriction prevents obesity- and intermittent hypoxia-induced cardiac remodeling in leptin-deficient ob/ob mice

Abstract: Background: Intermittent hypoxia (IH), a key characteristic of obstructive sleep apnea, is independently associated with cardiometabolic impairment. While endogenous leptin levels may provide cardioprotective effects against hypoxia, leptin resistance is common among obese individuals presenting with obstructive sleep apnea.Methods: Here, we assessed left ventricle (LV) function using M-mode echocardiography in lean wild-type, calorically-restricted ob/ob, and obese ob/ob mice before and after 6 days of IH to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
2
0
0
Order By: Relevance
“…All LV dimensions calculated using the Teichholz formula in wild-type control (12-week-old C57BL/6 mice) were consistent with those reported in previous studies by us [ 20 ] and another group [ 29 ].…”
Section: Methodssupporting
confidence: 87%
“…All LV dimensions calculated using the Teichholz formula in wild-type control (12-week-old C57BL/6 mice) were consistent with those reported in previous studies by us [ 20 ] and another group [ 29 ].…”
Section: Methodssupporting
confidence: 87%
“…•EDV = (7 x LVIDd All LV dimensions calculated using Teichholz formula in wild-type control (12-week-old C57BL/6 mice) shown in this study were consistent with those reported in previous studies by us [6] and another group [17].…”
Section: Physiological Experimentssupporting
confidence: 89%